Assessment of a new algorithm to detect atrial fibrillation in home blood pressure monitoring device among healthy adults and patients with atrial fibrillation. Issue 5 (1st February 2021) - Watanabe, Tomonori; Tomitani, Naoko; Yasui, Nobuhiko; Kabutoya, Tomoyuki; Hoshide, Satoshi; Kario, Kazuomi
Abstract: The authors evaluated the diagnostic accuracy of a new algorithm for detecting atrial fibrillation (AF) using a home blood pressure (BP) monitor. Three serial BP values were measured in 205 subjects with sinus rhythm and 75 subjects with AF confirmed by electrocardiogram. Irregular pulse peak (IPP) 15 was defined as follows: |interval of pulse peak ‐ the average of the interval of the pulse peak| ≥ the average of the interval of the pulse peak × 15%. Irregular heartbeat (IHB) was defined as follows: beats of IPP ≥ total pulse × 20%. The sensitivities of IPP15 for diagnosing AF defined as two or three IHBs of three readings were 1.0 and 0.99, and the corresponding specificities were 0.97 and 0.99, respectively. The algorithm using two or more IHBs of three readings in the setting of IPP15 had the highest diagnostic accuracy for AF.